Relation Between Deoxyribonucleic Acid and Intracytoplasmic Membranes in Escherichia coli O111a(1) - Altenburg, Betty C. (1970)
The possibility of a relationship between intracytoplasmic membranes and deoxyribonucleic acid (DNA) in Escherichia coli O111a(1) has been investigated. To facilitate this investigation, a simple enzymatic assay for the amount of internal membrane present in a culture was developed. This assay was then used to show that the appearance of intracytoplasmic membranes is accompanied by an increase in the DNA content of the cells. Electron micrographs have confirmed this observation and have shown DNA to be in contact with the intracytoplasmic membranes. Extensive membranes were observed at sites of apparently unsuccessful attempts at cell division. These observations led to the conclusion that the internal membrane formed by strain O111a(1) represents “extra” membrane, which is functional in that it contains sites for DNA replication, but is produced in excess because the organism is somehow defective in its regulation of membrane synthesis.